Solar Panels to Improve Reactive Current Compensation in Load Photoelectric Systems (Eurasian Research Bulletin, 2023)
This article photoelectric solar panels, photovoltaic systems opinions and feedback on DC converters and reactive power compensation electricity energy and economic efficiency is devoted to the improvement of the device controlled reactive current in the load of photovoltaic solar systems electricity energy and economic efficiency are presented in the table.